2016
DOI: 10.1038/ncomms10879
|View full text |Cite
|
Sign up to set email alerts
|

A conserved motif in JNK/p38-specific MAPK phosphatases as a determinant for JNK1 recognition and inactivation

Abstract: Mitogen-activated protein kinases (MAPKs), important in a large array of signalling pathways, are tightly controlled by a cascade of protein kinases and by MAPK phosphatases (MKPs). MAPK signalling efficiency and specificity is modulated by protein–protein interactions between individual MAPKs and the docking motifs in cognate binding partners. Two types of docking interactions have been identified: D-motif-mediated interaction and FXF-docking interaction. Here we report the crystal structure of JNK1 bound to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 72 publications
(84 reference statements)
0
54
0
Order By: Relevance
“…The role of the rhodanese domains in MKP1 and MKP5 in recruiting ERK2 and p38␣ is well-known: by mimicking a so-called docking motif, this surface enables strong interactions with several MAPKs (79). However, the docking site of JNK cannot bind rhodanese domains, so phosphatases targeting JNK bind in alternative ways (via their catalytic domain or by docking motifs, as observed in MKP5 and MKP7 [80,81]). In vivo studies suggest that MKP1 is not required for growth factor signaling; however, it is essential for immune cell activation, as MKP1 Ϫ/Ϫ mice show immune defects (82).…”
Section: Phosphatases and Feedback Mechanisms In Control Of Jnk Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the rhodanese domains in MKP1 and MKP5 in recruiting ERK2 and p38␣ is well-known: by mimicking a so-called docking motif, this surface enables strong interactions with several MAPKs (79). However, the docking site of JNK cannot bind rhodanese domains, so phosphatases targeting JNK bind in alternative ways (via their catalytic domain or by docking motifs, as observed in MKP5 and MKP7 [80,81]). In vivo studies suggest that MKP1 is not required for growth factor signaling; however, it is essential for immune cell activation, as MKP1 Ϫ/Ϫ mice show immune defects (82).…”
Section: Phosphatases and Feedback Mechanisms In Control Of Jnk Activitymentioning
confidence: 99%
“…signed to include docking domain peptides suggested that the FxFP site of JNKs is still functional (201); recent structural studies indeed suggest that this site mediates JNK1 interaction with the dual-specificity phosphatase MKP7 (81). Despite these alternative modes of interactions with the MAPKs, most JNK interactors use typical D-motifs to partner with JNKs (80).…”
Section: Jnk Recognition Of Its Partner Regulators and Substrates Docmentioning
confidence: 99%
“…JNK1δ displays a large deletion (of about 80 residues), lacking exons 6, 7 and 8. It does not contain the F-helix, shown to be crucial for kinases structural stability [42], nor the MAPK insert, involved in the binding of the phosphatase MKP7 [44] (Fig. 2).…”
Section: Properties Of the Orphan Transcriptsmentioning
confidence: 99%
“…Residues comprising the catalytic site were defined from the complex between human JNK3 and adenosine mono-phosphate (PDB code: 4KKE, resolution: 2.2Å), as those located less than 6Å away from the ligand. Residues comprising the D-site and the F-site were defined from the complexes between human JNK1 and the scaffolding protein JIP-1 (PDB code: 1UKH, resolution: 2.35 A [63]) and the catalytic domain of MKP7 (PDB code: 4YR8, resolution: 2.4 A [44]), respectively. They were detected as displaying a change in relative solvent accessibility >1Å 2 upon binding.…”
Section: Analysis Of Jnk Tertiary Structuresmentioning
confidence: 99%
“…There are 3 well‐defined MAPK pathways: ERK‐1/2, JNK‐1/2, and p38 (12). MAPK signaling efficiency and specificity are modulated by protein–protein interactions between individual MAPKs and the docking motifs in cognate binding partners (13). Important signaling pathways regulating responses of the cells to the infection and stress are via MAPKs (14).…”
mentioning
confidence: 99%